Recovery and Growth in Transition Economies 1990-97 : A Stylized Regression Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper analyzes the determinants of growth in 25 transition economies during 1990-97. The paper's main finding is that macroeconomic stabilization, structural reform, and reduction of government expenditures are key to achieving sustainable growth. Although the initial effect of reforms on output may be negative, over time the best growth performances are in those countries with the greatest progress in implementing reforms. The analysis also confirms that although adverse initial conditions hurt growth, their effect is small compared to the other factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet